Characterization of Insufficiency Fracture and Bone Metastasis After Radiotherapy in Patients With Cervical Cancer Detected by Bone Scan: Role of Magnetic Resonance Imaging - Zhong, Xi; Li, Jiansheng; Zhang, Linqi; Lu, Binggui; Yin, Jinxue; Chen, Zhijun; Zhang, Jian; Tang, Rijie (Frontiers in Oncology, 2019)
Abstract Background: Insufficiency fracture (IF) can show increased uptake on a bone scan (BS). IFs are often misinterpreted as bone metastases if the characteristic “Honda sign” (H-sign) is invisible. The purpose of the present study was to evaluate the utility of magnetic resonance imaging (MRI) alone for the characterization of IF and bone metastasis after radiotherapy in patients with cervical cancer detected by BS. Materials and methods: Our study included 40 patients with cervical cancer after radiotherapy that showed pelvic emerging increased uptake on a BS during follow-up. Then further MRI examination was performed in all patients. Two radiologists independently reviewed the MR images, and the sensitivity, specificity and accuracy were calculated based on the mean scores. Diagnostic validity of the inter-observer was calculated by using kappa statistics. The gold standard was based on radiologic findings, clinical data and follow-up at least 12 months. Results: A total of 57 emerging bone lesions detected at BS were identified in the reference standard, including 43 IFs and 14 bone metastases. Only 20 patients showed a “H-sign” on the BS images. Using MRI analysis, all lesions detected by BS were found in MRI by both radiologists. On average, the sensitivity, specificity and accuracy for distinguishing IFs from bone metastases were 95.3% (41/43), 92.8% (13/14) and 94.7% (54/57), respectively. The inter-observer variability was determined to be very good (kappa value = 0.962). Conclusions: MRI is a reliable diagnostic technique for the further characterization of emerging lesions detected by BS, MRI shows great diagnostic efficiency in the differentiation of IF and bone metastasis.